Marketing Intercollegiate Athletics at the NCAA Division III Level - Cheryl Robinson (Journal of Applied Sports Management, 2010)
This article is featured as part of a partnership between The Sports Business Exchange (TSBX) and the Journal of Sport Administration & Supervision that involves cross-publication of selected articles on various sport business topics aimed at improving practices of business professionals in the sport industry. TSBX is a sports business trade journal available in both print and online formats, which publishes articles on current events, trends, research, and concerns written from the perspectives of young sport business professionals. The following article appears in the pages of JSAS unabridged as published by TSBX and with the permission of TSBX and the author(s), who own all rights to the work and have granted specific permission to JSAS to reprint. Permission for further reproduction and/or distribution must be obtained from TSBX and the author(s).